O assessor pedagógico: narrativas, processos autoformativos e formação continuada - Souza, Mônica Cristina de (2025)
The central question of this research is: How does the pedagogical advisor organize, experience, and perceive her self-formative process, and what value does she attribute to it? This question was revisited with each reading and analysis of the material produced through professionalfocused narratives, a participant characterization questionnaire, and individual dialogue sessions. The participants who contributed to this study were ten external pedagogical advisors working for a private educational system. The professional-focused narratives revealed the perceived and lived life stories of the participants, and through the excerpts selected for analysis, it was possible to identify the beliefs, values, and theoretical constructs that underpin their know how to do and know how to be in the professional sphere. The research adopted a qualitative approach, and based on André (1983), Lüdke & André (1986), and Sigalla & Placco (2022), prose analysis was the chosen method for examining the data, considering the interplay with the context and the theoretical framework supporting the study while respecting the participants’ individual perspectives. Assuming that narrating one’s experiences fosters deeper self-understanding, this study aimed to analyze the paths external pedagogical advisors take in pursuit of their self-formation and how this process manifests in their daily work. The theoretical framework draws on the works of Imbernón (2011), Placco (2006; 2008), Placco & Souza (2006), Placco & Almeida (2018), Nóvoa (1992, 2009), Marcelo García (1999), Tardif (2014), Huberman (1989), Pineau (2014), Passos (2016), Freire (1981, 1987, 1993, 1994, 1996, 2001), Souza (2006, 2009), Josso (2007), Passeggi (2011), and Delory-Momberger (2012), allowing for an intertwining comprehension of the theoretical field on self-formation, lifelong learning, continuing education, narratives, and self-writing. The analysis established four broad categories: Initial influences and motivations; Choosing education and career building; Selfformation practices and reflection; and Values and commitments to Education, which together illuminated the self-formative paths these advisors constructed. As one of the outcomes, parameters were identified to guide self-formation processes for other professionals in the field of external pedagogical advising